Trajectories and determinants of adolescents' nicotine product use risk among U.S. adolescents in a nationally representative sample of longitudinal cohort. (May 2021) - Kwon, Elizabeth; Adams, Zachary; Seo, Dong-Chul
Highlights: We identified 5 latent trajectories of nicotine product use risk among adolescents. The results reveal segmentation of a key target population for intervention efforts. Daily SNS use is associated with increased risk of nicotine product use. Marijuana use at Wave 1 was the strongest predictor of stable risk groups. Abstract: Introduction: To understand the heterogeneous longitudinal trends in adolescent nicotine product use risk, we investigated the trajectories and determinants of nicotine product use among adolescents. Methods: Using Waves 1–4 (Years 2013–2018) data of the Population Assessment of Tobacco and Health Study, we conducted group-based trajectory modeling to identify groups of individuals who followed homogeneous trajectories of nicotine product use risk over time and weighted multinomial logistic regression to examine relative risk ratios (RRRs) of different levels of predictors of group membership in each identified trajectory. Results: For adolescents, who were 12–17 years old at baseline (N = 10, 086), 5 trajectory groups emerged: (1) nonusers (73.7%); (2) stable low to moderate risk of developing poly use (5.0%); (3) gradual increase in risk of poly use (12.8%); (4) rapid linear increase in risk of poly use until Wave 3 and then plateauing for cigarettes or slightly diminishing for e-cigarettes and other tobacco products at Wave 4 (4.6%); and (5) stable moderate to high risk of poly use (3.9%). Adolescents who used social network services daily at Wave 1 were more likely to belong to each of the four trajectory groups compared to nonusers (RRRs ranging from 1.43 to 2.04). Conclusions: The current study findings imply that the majority of adolescents who initiated any nicotine product use have an elevated risk of transitioning to poly users. Risk and protective factors for different risk patterns are discussed.